If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = p + -1(-6) Multiply -1 * -6 19 = p + 6 Reorder the terms: 19 = 6 + p Solving 19 = 6 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 19 + -1p = 6 + p + -1p Combine like terms: p + -1p = 0 19 + -1p = 6 + 0 19 + -1p = 6 Add '-19' to each side of the equation. 19 + -19 + -1p = 6 + -19 Combine like terms: 19 + -19 = 0 0 + -1p = 6 + -19 -1p = 6 + -19 Combine like terms: 6 + -19 = -13 -1p = -13 Divide each side by '-1'. p = 13 Simplifying p = 13
| 4x+1-7x=-8 | | 0.2x-0.6(4-x)=-0.4 | | x^2-5x=8x-3 | | 53c-3c+15=16.84 | | 15x^2+10x-40=0 | | 3-2(b-5)=7 | | 2x-2(-4-3x)=-10+8x | | x^4+16y^4=32 | | ln(t+1)=ln(3)(t-4) | | 4+4+3=11 | | abs(3x+5)=abs(3x+4) | | t^2-t-40=0 | | 4+-1y=x | | 0.2x-0.6(4-x)=0.4 | | 3x+3x-6=-6 | | -7x+5=19 | | 6+xy=7x-8y | | ln(5x)-ln(3)=6 | | 8x+5=2x-37 | | 6x+40=40 | | 0.2y+0.9=0.4-0.3y | | 10(z+3)-4(z-4)+3(z-3)= | | 7-y=-13 | | 2=6(x+8)-7x | | (3y+7)(9y^2+42y+49)= | | 9(x+4)=7+9x | | 0.2y+0.9=0.2-0.5 | | 16x-(4-5d)=-67 | | 8+2x=46 | | 5e+2=6 | | 3/4(3)-12=1/2(3)-6 | | -9x+3y=7 |